Customer on the move: Strategic implications of mobile banking for banks and financial enterprises - Rajnish Tiwari; Stephan Buse; Cornelius Herstatt (Hamburg University of Technology (TUHH), Institute for Technology and Innovation Management (TIM), 2006)
The increased need/wish for mobility amongst various sections of the society, particularly amongst professionally active groups, is confronting credit institutions (banks) and other enterprises offering financial services, with challenges to adjust their service portfolio in a way to best suit the needs of their customers. On the other hand it also opens up a new arena of opportunities by making it possible to offer innovative, value-added services so as to not only cater to the needs arising out of the mobility but also by actively inducing demand for new, mobility-centric services. This paper examines strategic implications of these changes in customer behavior as perceived by the banks. It introduces the findings of a bank survey conducted by the authors in Germany. The survey discovered that banks expect Mobile Banking to gain greater relevance in near future and are positioning themselves not to be left behind.
Keywords: 650; Mobile Banking; Mobile Financial Services; Mobile Commerce; Mobile Business; Multi-channel strategy